Norovirus Vaccines: Current Clinical Development and Challenges - Ming Tan (Pathogens, 2021)
Noroviruses are the major viral pathogens causing epidemic and endemic acute gastroenteritis with significant morbidity and mortality. While vaccines against norovirus diseases have been shown to be of high significance, the development of a broadly effective norovirus vaccine remains difficult, owing to the wide genetic and antigenic diversity of noroviruses with multiple co-circulated variants of various genotypes. In addition, the absence of a robust cell culture system, an efficient animal model, and reliable immune markers of norovirus protection for vaccine evaluation further hinders the developmental process. Among the vaccine candidates that are currently under clinical studies, recombinant VP1-based virus-like particles (VLPs) that mimic major antigenic features of noroviruses are the common ones, with proven safety, immunogenicity, and protective efficacy, supporting a high success likelihood of a useful norovirus vaccine. This short article reviews the recent progress in norovirus vaccine development, focusing on those from recent clinical studies, as well as summarizes the barriers that are being encountered in this developmental process and discusses issues of future perspective.